2011
DOI: 10.1113/jphysiol.2011.210294
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Nrf2–Keap1 antioxidant defence pathway for neurovascular protection in stroke

Abstract: Endogenous defence mechanisms by which the brain protects itself against noxious stimuli and recovers from ischaemic damage are a key target of stroke research. The loss of viable brain tissue in the ischaemic core region after stroke is associated with damage to the surrounding area known as the penumbra. Activation of the redox-sensitive transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) plays a pivotal role in the cellular defence against oxidative stress via transcriptional upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 86 publications
(174 reference statements)
2
127
0
1
Order By: Relevance
“…Activation of oxidative/ inflammatory stress signaling cascades by drugs of abuse is the primary mechanism for increased endothelial activation and leukocyte migration across the BBB into the brain. Recent studies from our group (Sajja et al, 46 Naik et al, 115 and Prasad et al 146 ) and other groups (Alfieri et al 147 and Sandberg et al…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Activation of oxidative/ inflammatory stress signaling cascades by drugs of abuse is the primary mechanism for increased endothelial activation and leukocyte migration across the BBB into the brain. Recent studies from our group (Sajja et al, 46 Naik et al, 115 and Prasad et al 146 ) and other groups (Alfieri et al 147 and Sandberg et al…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…28,29 The results provide the first demonstration of miR-424 acting as a modulator of antioxidants after I/R by increasing the levels of MnSOD and EcSOD and stimulating MnSOD activity. Although SOD expression in the peri-infarct cortex was unaltered after 24 hours of reperfusion, MnSOD activity increased; in primary cortical neurons, MnSOD activity decreased after 6 hours of exposure to H 2 O 2 .…”
mentioning
confidence: 91%
“…The function of HO-1 is to catalyze heme to biliverdin, carbon monoxide and iron. It has been previously reported that Nrf-2 activation protects the neurons from ischemia (22). Under physiological conditions, Nrf2 is located in the cytosol and binds to Kelch-like ECH-associated protein 1 (Keap1).…”
Section: Introductionmentioning
confidence: 99%